Analisis Kesiapan Digital Pemerintahan Negeri Batu Merah menuju Smart Village - Muhtar Muhtar; Rukoyah Rukoyah; Yustina Sopacua (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the digital readiness of the Negeri Batu Merah Government in Ambon City in supporting the implementation of a smart village. The study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research informants consisted of village government officials, administrative staff, and community members as users of public services. The results showed that the Negeri Batu Merah Government has begun implementing administrative digitalization through the use of computers, digital communication media, and electronic archive management in public services. The government’s digital readiness is supported by the commitment of local authorities, the availability of basic technological facilities, and the increasing public demand for fast and effective services. However, the implementation of government digitalization still faces several challenges, including limited internet infrastructure, low human resource capacity among government officials, budget constraints, and limited digital literacy within the community. This study concludes that the development of a smart village in Negeri Batu Merah requires strengthening digital infrastructure, improving the competencies of government officials, and increasing community participation to ensure that digital transformation can be implemented optimally and sustainabl.